Arsenite Oxidation by a Newly Isolated Betaproteobacterium Possessing arx Genes and Diversity of the arx Gene Cluster in Bacterial Genomes - Ospino, Melody Cabrera; Kojima, Hisaya; Fukui, Manabu (Frontiers in Microbiology, 2019)
Microbes play essential roles in arsenic transformation in the environment. Microbial arsenite oxidation is catalyzed by either of two distantly related arsenite oxidases, referred to as AIO and ARX. The arx genes encoding ARX and its regulatory proteins were originally defined in the genomes of gammaproteobacteria isolated from an alkaline soda lake. The arx gene cluster has been identified in a limited number of bacteria, predominantly in gammaproteobacteria isolated from lakes characterized by high pH and high salinity. In the present study, a novel arsenite-oxidizing betaproteobacterium, strain M52, was isolated from a hot spring microbial mat. The strain oxidized arsenite under nitrate-reducing conditions at nearly neutral pH. Genome analysis revealed that the strain possesses the arx gene cluster in its genome and lacks genes encoding AIO. Inspection of the bacterial genomes available in the GenBank database revealed that the presence of this gene cluster is restricted to genomes of Proteobacteria, mainly in the classes Gammaproteobacteria and Betaproteobacteria. In these genomes, the structure of the gene cluster was generally well conserved, but genes for regulatory proteins were lacking in genomes of strains belonging to a specific lineage. Phylogenetic analysis suggested that ARX encoded in the genomes can be divided into three groups, and strain M52 belongs to a group specific for organisms living in low-salt environments. The ArxA protein encoded in the genome of strain M52 was characterized by the presence of a long insertion, which was specifically observed in the same group of ARX. In clone library analyses with a newly designed primer pair, a diverse ArxA sequence with a long insertion was detected. Among the isolated bacterial strains whose arsenite oxidation has been demonstrated, strain M52 is the first betaproteobacterium that possesses the arx genes, the first strain encoding ARX of the group specific for low-salt environments, and the first organism possessing the gene encoding ArxA with a long insertion.